Design of a Varying Die-plate Fish Feed Pelletizer and Performance Evaluation Using a Non-conventional Feed Sources - Sunmonu, Musliu Olushola; Odewole, Michael Mayokun; Falua, Kehinde James (Applied Science and Engineering Progress, 2018)
An electrically-operated fish feed pelletizer was designed, fabricated and tested. The machine was incorporated with an easily detachable die plates capable of extruding different sized feed. Performance evaluation of the machine was carried out using a non-conventional feed resources of fermented citrus and plantain peels each formulated with fish feed constituents such as fish oil and groundnut cake prepared at a moisture content of 20% wet basis. The performance indices considered in the evaluation of the pelletizer were pelleting efficiency, percentage recovery and percentage of unpelleted feed. Results obtained when 250 g of formulated feed was introduced into the pelletizer showed an higher pelleting efficiency (91.50%), percentage recovery (73.20%) and a lower percentage of unpelleted feed (26.81%) when die plate having screen size of 5 mm holes was used. Evaluation using die plate having 3 mm holes showed that the average values for pelleting efficiency, percentage recovery, and percentage unpelleted feed were 82.09, 65.67 and 35.73% respectively. Statistical analysis of the performance indices with respect to the 3 mm and 5 mm die sizes showed that performance indices had significant difference on formulated feed having fermented citrus peel while not statistically significant for feed formulated with fermented plantain peel at p < 0.05.